2020
DOI: 10.1007/s10067-020-05444-2
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility to biologics and its impact on disease activity and quality of life in patients with rheumatoid arthritis in Kuwait

Abstract: Objective Biologics are indicated in rheumatoid arthritis (RA) in case of persistent high disease activity despite conventional disease-modifying anti-rheumatic drugs (cDMARDs) or patients with contraindications to cDMARDs or poor prognostic factors. The purpose of this study was to compare the prescription rates of biologics in Kuwaiti and non-Kuwaiti patients and to assess whether this had an impact on disease activity and quality of life in RA patients. Methods Data were extracted from the Kuwait Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Based on this, this study explores the relationship between drug accessibility and HRQoL of patients with chronic diseases, and finds that the increase in the accessibility of medicines has significant positive impact on the health utility value of patients with chronic diseases. This assumption will be in line with other studies: Kuwaiti patients with rheumatoid arthritis have significantly reduced joint swelling and reduced disease activity due to the higher rate of biomedicine use, and the health assessment questionnaire scores higher (40). In order to ensure the accessibility of medicines, a number of studies have provided suggestions for national medicine policies.…”
Section: Discussionsupporting
confidence: 74%
“…Based on this, this study explores the relationship between drug accessibility and HRQoL of patients with chronic diseases, and finds that the increase in the accessibility of medicines has significant positive impact on the health utility value of patients with chronic diseases. This assumption will be in line with other studies: Kuwaiti patients with rheumatoid arthritis have significantly reduced joint swelling and reduced disease activity due to the higher rate of biomedicine use, and the health assessment questionnaire scores higher (40). In order to ensure the accessibility of medicines, a number of studies have provided suggestions for national medicine policies.…”
Section: Discussionsupporting
confidence: 74%
“…However, management practices for RA, healthcare infrastructure, regulatory approval processes and the level of financial burden on patients vary considerably across countries in Africa and the Middle East [ 34 , 39 ]. A study in Kuwait reported lower disease activity and a positive impact on overall physical function in patients with easy access to biologic DMRDs compared with those without easy access [ 57 ]. Similar results were observed in a study in the United Arab Emirates where only 43% of patients received DMARDs [ 55 ], underlining the importance of easy access to highly effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In RA, as a chronic disease, the presentation and course of the disease differ among individual patients. In recent studies, gene detection in RA has been frequently discussed, but the results were rarely combined with clinical indicators and the patients' quality of life ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%